(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The phrase "customer satisfaction" is commonly used in marketing. It evaluates how well a company’s goods and services meet or surpass those of its clients. "The number of customers, or percentage of total customers, whose reported experience with a firm, its products, or its services (ratings) exceeds specified satisfaction goals." Customer satisfaction (abbreviated CSAT) is a marketing term that is frequently used. It is a measure of how well a company’s products and services meet or exceed customer expectations. "The number of customers, or percentage of total customers, whose reported experience with a firm, its products, or its services (ratings) exceeds specified satisfaction goals." As part of its ongoing Common Language in Marketing Project, the Marketing Accountability Standards Board (MASB) endorses the definitions, purposes, and constructs of classes of measures found in Marketing Metrics. In a survey of nearly 200 senior marketing executives, 71% said a customer satisfaction metric was very useful in managing and monitoring their businesses.